The developmental and genetic bases of apetaly in Bocconia frutescens (Chelidonieae: Papaveraceae) (2016)
ABSTRACT: Background: Bocconia and Macleaya are the only genera of the poppy family (Papaveraceae) lacking petals; how‐ ever, the developmental and genetic processes underlying such evolutionary shift have not yet been studied. Results: We studied floral development in two species of petal‐less poppies Bocconia frutescens and Macleaya cordata as well as in the closely related petal‐bearing Stylophorum diphyllum. We generated a floral transcriptome of B. frutescens to identify MADS‐box ABCE floral organ identity genes expressed during early floral development. We performed phylogenetic analyses of these genes across Ranunculales as well as RT‐PCR and qRT‐PCR to assess loci‐ specific expression patterns. We found that petal‐to‐stamen homeosis in petal‐less poppies occurs through distinct developmental pathways. Transcriptomic analyses of B. frutescens floral buds showed that homologs of all MADS‐box genes are expressed except for the APETALA3‐3 ortholog. Species‐specific duplications of other ABCE genes in B. frute- scens have resulted in functional copies with expanded expression patterns than those predicted by the model. Conclusions: Petal loss in B. frutescens is likely associated with the lack of expression of AP3‐3 and an expanded expression of AGAMOUS. The genetic basis of petal identity is conserved in Ranunculaceae and Papaveraceae although they have different number of AP3 paralogs and exhibit dissimilar floral groundplans.